2. Social Competence and the Profile of the Student Aspiring to the Teaching Career - Jitaru Oana; Bobu Roxana; Anghel Ona Ionica (Review of Artistic Education, 2023)
Along with the specific skills developed during psycho-pedagogical training programs of future teachers, the expected attitudes that a teacher should perform are also relevant. These attitudes can outline the area of social competence - without which the activity of a future teacher is ineffective. This socio-emotional behaviour is based on the ability to listen and learn from the other, to understand what the child feels by supporting and respecting him at the same time, the ability to create relationships. In this context, we consider that the option for the teaching profession, along with the logical arguments invoked by each applicant, is also based on justifications such as: it suits my way of being, I like to explain, I help others to understand, I was told that I know how to listen, I feel good around others, I am a person willing to offer support to others, etc. Starting from these aspects, we set out to investigate the profile of the student following the psycho-pedagogical module regarding the following dimensions - assertiveness, empathy, self-presentation and the ability to develop positive interpersonal relationships. The working hypothesis is that in the profile of the student preparing for the teacher profession we find these dimensions or specific elements. We also hypothesized that a high level of assertiveness would also result in a high level of problem-solving skills. The conducted investigation highlighted the fact that indeed the choice of a training path in the teaching career is based on an above average level of the variables assertiveness, self-presentation and the ability to develop positive interpersonal relationships with others. It can be observed, however, that the ability to resolve conflicts is at a low level, which may indicate the difficulty of students to effectively apply communication strategies in managing difficult relationships. We conclude that the activities of self-knowledge and personal development integrated in the psycho-pedagogical training programme are essential for the development of self-evaluation skills and for applying the self-perceived potential of students in effective social interactions.